Penggunaan Prezi untuk Media Pembelajaran Matematika Materi Fungsi - Rohiman, Rohiman; Anggoro, Bambang Sri (Desimal: Jurnal Matematika, 2019)
This study aims to develop prezi-based mathematics learning media to increase interest in learning in the function material. The media developed is a mathematics learning media using Prezi software. This type of research is research and development (Research and Development) using an adapted research and development model which includes stages: (1) Analysis; (2) Design; (3) Development; (4) Trial (Implementation). The subjects of this research trial were 33 eighth grade students with function material. In this development research with the main objectives as product development and testing the effectiveness of the product in achieving the objectives in the study. Data collection instruments used were media validation questionnaire, material validation questionnaire, and student response questionnaire. The main result of this research is mathematics learning media using Prezi software. The quality of mathematics learning media using Prezi software is very good based on the results of media expert validation with a score of 93% and based on material experts is good with a score of 77.5%, and the response of students to learning media is very good with a score of 83.9% using a scale Likert.